2012
DOI: 10.1016/j.rehab.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Acquired visual field defects rehabilitation: Critical review and perspectives

Abstract: Visual field deficit (VFD) is one of the most commonly observed symptoms following brain injury. Persistent VFD and defective exploratory oculomotor scanning patterns often cause severe impairment in daily activities, particularly as regards visual exploration and reading. Homonymous hemianopia is consequently a powerful negative predictor of patient outcome. In spite of these quantitative and qualitative factors, there currently exists no consensus on rehabilitative therapy and treatment. Different approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 109 publications
0
23
0
Order By: Relevance
“…VRT has been criticised due to inconsistent outcomes in previous research, ranging from significant improvements to minimal or no effects at all. A source of this inter-subject variation could be that the perimetric techniques are subjective and biased towards a positive outcome and that VRT outcomes are confounded by eye movements (Pouget et al, 2012;Reinhard et al, 2005). Indeed, the reliability of an extension of the visual field from perimetric data can be hampered by insufficient eye fixation control.…”
Section: The Controversy Of Vrt Efficacymentioning
confidence: 99%
“…VRT has been criticised due to inconsistent outcomes in previous research, ranging from significant improvements to minimal or no effects at all. A source of this inter-subject variation could be that the perimetric techniques are subjective and biased towards a positive outcome and that VRT outcomes are confounded by eye movements (Pouget et al, 2012;Reinhard et al, 2005). Indeed, the reliability of an extension of the visual field from perimetric data can be hampered by insufficient eye fixation control.…”
Section: The Controversy Of Vrt Efficacymentioning
confidence: 99%
“…Various strategies have been adopted for visual system rehabilitation following injury. Chief among them (Das & Huxlin 2010, Pelak et al 2007, Pouget et al 2012, Schofield & Leff 2009 are (a) relocating the visual field via prismatic correction, (b) teaching compensatory strategies for oculomotor exploration of the blind field, and (c) improving residual detection capability and recovering lost visual function (improving visual perception). Recovery induced by compensatory strategies (a) and (b) is not discussed in this review, but instead the focus is on the recovery of visual perception.…”
Section: Potential For Recovery After Lesions Of the Adult Visual Sysmentioning
confidence: 99%
“…In most cases reported, visual expansion did not exceed 5% (Kasten and Sabel, 1995; Kasten et al, 1998b) and was less pronounced in others studies (from 1° to 6.7°) (Pommerenke and Markowitsch, 1989; Kerkhoff et al, 1992, 1994) or even absent (Balliet et al, 1985). Some authors suggested that visual field improvements could be an artefact of eye movements (Horton, 2005a; Reinhard et al, 2005) and that controversial results could be related to (1) the perimeter techniques employed; (2) lesion localization; or (3) explanatory mechanisms (Pouget et al, 2012). …”
Section: Reorganization After Rehabilitationmentioning
confidence: 99%